Excessive Pricing Pada Penjualan Produk Masker Ditengah Pandemi Covid-19 Dikaitkan Dengan Undang-Undang Nomor 5 Tahun 1999 - Edwin Wira Adikusuma Hartawan (Faculty of Law, Universitas Airlangga, 2021)
AbstractDuring the COVID-19 pandemic, a health mask is one of the products used as personal protective equipment from transmission of the COVID-19 virus. The increasing number of requests which was not followed by an increase in the amount of production of health mask products was used by some irresponsible persons who hoarded health masks and resold them at multiple prices. The act of over-setting high prices by taking advantage of the dominant position of business actors referred to as excessive pricing. However, KPPU as a business competition supervisory agency through Press Release No. 14 / KPPU-PR / III / 2020 stated that there were no violations by business actors in the trade in health mask products. So further research is needed to prove whether there are business actors who set an excessive price in the trade in health mask products during the COVID-19 pandemic outbreak or whether the increase in prices for health mask products is only an impact of imbalances in market mechanisms in the form of increased demand which is not followed by an increase production by health mask business actors. Keywords: Excessive Price; Business Competition; Abuse of Dominant Position.AbstrakDalam masa pandemi COVID-19 ini, masker kesehatan merupakan salahsatu produk yang digunakan sebagai alat pelindung diri dari penularan virus COVID-19. Jumlah permintaan yang meningkat dan tidak diikuti oleh peningkatan jumlah produksi atas produk masker kesehatan dimanfaatkan oleh beberapa oknum tidak bertanggung jawab yang melakukan penimbunan atas masker kesehatan dan menjualnya kembali dengan harga berkali-kali lipat.Tindakan menetapkan harga tinggi secara berlebihan dengan memanfaatkan posisi dominan pelaku usaha disebut sebagai excessive pricing. Namun, KPPU sebagai lembaga pengawas persaingan usaha melalui Siaran Pers No.14/KPPU-PR/III/2020 menyatakan belum adanya pelanggaran oleh pelaku usaha dalam perdagangan produk masker kesehatan. Maka diperlukan penelitian lebih lanjut untuk membuktikan apakah terdapat pelaku usaha yang menetapkan excessive price dalam perdagangan produk masker kesehatan dalam masa wabah pandemi COVID-19 ini ataukah peningkatan harga pada produk masker kesehatan hanya merupakan dampak ketimpangan pada mekanisme pasar berupa peningkatan permintaan yang tidak diikuti dengan peningkatan produksi oleh pelaku usaha masker kesehatan.Kata Kunci: Excessive Price; Persaingan usaha; Penyalahgunaan posisi dominan.